Abusive Supervision, Affective Commitment, Customer Orientation, and Proactive Customer Service Performance: Evidence From Hotel Employees in China - Zang, Dexia; Liu, Chang; Jiao, Yan (Frontiers in Psychology, 2021)
Abusive supervision is quite common in the service industry. And employees' proactive customer service performance is quite essential for the long-term development of service enterprises. This study enriches the antecedents of proactive customer service performance from a new theoretical perspective by incorporating the analysis of abusive supervision into the theoretical framework, and fills the research gap between customer orientation and proactive customer service performance. Based on Affective Events Theory and Social Cognitive Theory, this study established the structure equation model between abusive supervision and proactive customer service performance, mediating by affective commitment and customer orientation. Utilizing structural equation modeling, a negative association between abusive supervision and proactive customer service performance was found and affective commitment and customer orientation act as the mediators between abusive supervision and proactive customer service performance. In addition, the implications for future study were also discussed.